Oligogalacturonides: plant damage-associated molecular patterns and regulators of growth and development - Ferrari, Simone; Savatin, Daniel V.; Sicilia, Francesca; Gramegna, Giovanna; Cervone, Felice; De Lorenzo, Giulia (Frontiers in Plant Science, 2013)
Oligogalacturonides (OGs) are oligomers of alpha-1,4-linked galacturonosyl residues released from plant cell walls upon partial degradation of homogalacturonan. OGs are able to elicit defence responses, including accumulation of reactive oxygen species and pathogenesis-related proteins, and protect plants against pathogen infections. Recent studies demonstrated that OGs are perceived by Wall-Associated Kinases and share signalling components with microbe-associated molecular patterns. For this reason OGs are now considered true damage-associated molecular patterns that activate the plant innate immunity and may also be involved in the activation of responses to mechanical wounding. Furthermore, OGs appear to modulate developmental processes, likely through their ability to antagonize auxin responses. Here we review our current knowledge on the role and mode of action of this class of oligosaccharides in plant defence and development.